Implementation of an ISO 45001:2018-Based OH&S Management System to Reduce Workplace Accidents in Construction Companies (SCIÉNDO INGENIUM, 2026)
This research aimed to develop and implement an Occupational Health and Safety Management System (OHSMS) based on ISO 45001:2018, in order to reduce workplace accidents in a construction company. A diagnostic assessment of regulatory compliance and accident history was conducted during 2023, identifying key weaknesses in risk management. Based on this assessment, an OHSMS adapted to the organization's characteristics was developed, implemented, and evaluated using accident and compliance indicators. The results showed an 87.5% reduction in workplace accidents, from eight cases in 2023 to one in 2024. Furthermore, the degree of alignment with the requirements of ISO 45001:2018 increased from 21.6% to 98.9% after the internal audit, demonstrating significant progress in preventative management. These results show that the implemented system directly contributed to reducing occupational risks and consolidating safety-oriented practices. Consequently, it was verified that the implementation of an OSHMS based on this standard significantly strengthens preventive performance in activities specific to the construction sector.
Keywords: Workplace accident; risk management; substandard act; substandard condition; risk assessment and/or risk prevention; legal compliance